Predictors of Quality of Life in Patients with Heart Failure: A Literature Review - Ah. Yusuf (Journal of Global Pharma Technology, 2020)
Heart failure (HF) is a chronic disease characterized by reduce heart efficiency affecting patients’ quality of life (QoL). Patients with HF report lower QoL compared with general population and other patients with chronic disease. There are multidimensional factors affecting QoL. Therefore, it is important to identify factors that could be associated with changes in QoL to improve outcomes. The aim of this study was to identify significantly factors related to QoL in patients with HF according to the available literatures. The literatures were searched in appropriate database, using PICO framework, from January 2012 until August 2018. Eighteen relevant articles were found and reviewed. Factors that are significantly related to QoL in patient with HF can be grouped into 5 categories, i.e. physical factors include physical symptoms, physical activity, functional status, duration of HF, and multiple hospitalization; psychosocial factors include depression, optimism, exercise self-efficacy, and living independently; behavioral factors include self-care engagement, water and sodium restriction; spiritual factors include acceptance of illness and existensial well-being; and demographic characteristics include age, sex, education, economic and employment status. This review provides insight on potentially factors affecting QoL. Proper intervention in modifying those factors is expected to improve the quality of life. Keywords: Heart failure, Quality of life, Health-related quality of life, Predictors.